ZULFIYA KUROLBOY KIZI AND HER VIEWS ON MODERN REALITY - Umida ANNAKULOVA ABDULLAYEVNA (Scholar Express Journal, 2023)
This article is written about Zulfiya Kurolboy and her views on modern reality. Also, while studying the stages of the development of the literature of each country, we can observe the influence and similar manifestations of the literature of other neighboring or relatively distant countries in each stage to a certain extent. Relations between Uzbek literature and literature in the Arabic language go back to the distant past, and these literary relations continue to this day.
Keywords: Uzbek literature; women's prose; the spiritual world of heroes; traditions